(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article evaluates the effectiveness of a methodology for teaching Biochemistry in higher education institutions based on Artificial Intelligence (AI) and Virtual Reality (VR) technologies through pedagogical experimental work. During the research, an instructional methodology based on the use of AI tools, 3D visualizations, and VR technologies was developed and tested in experimental and control groups. The obtained results showed a significant improvement in students’ theoretical knowledge, practical skills, independent thinking, and learning motivation. The results of the statistical analysis confirmed the positive impact of the developed methodology on improving educational effectiveness.